The lean practitioner's field book : proven, practical, profitable and powerful techniques for making lean really work - Protzman, Charles (CRC Press, 2016)
"While there are numerous Lean Certification programs, most companies have their own certification paths whereby they bestow expert status upon employees after they have participated in or led a certain number of kaizen events. Arguing that the number of kaizen events should not determine a person's expert status, The Lean Practitioner's Field Book: Proven, Practical, Profitable and Powerful Techniques for Making Lean Really Work outlines a true learning path for anyone seeking to understand essential Lean principles. The book includes a plethora of examples drawn from the personal experiences of its many well-respected and award-winning contributors. These experts break down Lean concepts to their simplest terms to make everything as clear as possible for Lean practitioners. A refresher for some at times, the text provides thought-provoking questions with examples that will stimulate learning opportunities. Introducing the Lean Practitioner concept, the book details the five distinct Lean Practitioner levels and includes quizzes and criteria for each level. It highlights the differences between the kaizen event approach and the Lean system level approach as well as the difference between station balancing and baton zone. This book takes readers on a journey that begins with an overview of Lean principles and culminates with readers developing professionally through the practice of self-reliance. Providing you with the tools to implement Lean tools in your organization, the book includes discussions and examples that demonstrate how to transition from traditional accounting methods to a Lean accounting system. The book outlines an integrated, structured approach identified by the acronym BASICS (baseline, analyze, suggest solutions, implement, check, and sustain), which is combined with a proven business strategy to help ensure a successful and sustainable transformation of your organization"--Amazon.com